Peranan Kelompok Referensi Terhadap Perilaku Pembeli Individual - M. Ikhwan Rahmanto (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2005)
Orientation of new marketing concept is satisfaction of consumer. The orientation oblige producer more understand cosumer behavior in decision making of purchasing. Reference group have influence to individual buyer behaviour. The purpose of study of reference group role is to support marketing decision making